The molecular landscape of colitis-associated carcinogenesis. Issue 4 (April 2017) - Saraggi, Deborah; Fassan, Matteo; Mescoli, Claudia; Scarpa, Marco; Valeri, Nicola; Michielan, Andrea; D'Incá, Renata; Rugge, Massimo
Abstract: In spite of the well-established histopathological phenotyping of IBD-associated preneoplastic and neoplastic lesions, their molecular landscape remains to be fully elucidated. Several studies have pinpointed the initiating role of longstanding/relapsing inflammatory insult on the intestinal mucosa, with the activation of different pro-inflammatory cytokines (TNF-α, IL-6, IL-10, IFN-γ), chemokines and metabolites of arachidonic acid resulting in the activation of key transcription factors such as NF-κB. Longstanding inflammation may also modify the intestinal microbiota, prompting the overgrowth of genotoxic microorganisms, which may act as further cancer promoters. Most of the molecular dysregulation occurring in sporadic colorectal carcinogenesis is documented in colitis-associated adenocarcinoma too, but marked differences have been established in both their timing and prevalence. Unlike sporadic cancers, TP53 alterations occur early in IBD-related carcinogenesis, while APC dysregulation emerges mainly in the most advanced stages of the oncogenic cascade. From the therapeutic standpoint, colitis-associated cancers are associated with a lower prevalence of KRAS mutations than the sporadic variant. Epigenetic changes, including DNA methylation, histone modifications, chromatin remodeling, and non-coding RNAs, are significantly involved in colitis-associated cancer development and progression. The focus now is on identifying diagnostic and prognostic biomarkers, with a view to ultimately designing patient-tailored therapies.